Cryptocurrency As A Means of Investment and Payment on Islamic Law Perspective - Wandri, Amra; Arsal, Arsal; Rahmiati, Rahmiati; Imran, Maizul (Alhurriyah, 2023)
Advances in science and technology affect people's lifestyles, including the field of muamalah. Cryptocurrency is used as a means of investment and payment transactions in the modern era. The need for ijtihad to address the presence of digital currencies in Islamic law because it is a new problem and there is a discourse of contemporary Indonesian scholars who approve and prohibit it. The research aims to uncover and find legal solutions of the use of Cryptocurrency as an investment and payment tool. The research method uses descriptive-qualitative literature studies. The results of the study found that the use of Cryptocurrency as an investment tool prohibited because there is a vagueness of the object, has no asset guarantee and high elements of gharar. While its function as a medium of exchange in the digital era in Islamic law is not prohibited on the condition that the transaction has agreed and understood each other's mechanisms and there is legality from the government.Kemajuan sains dan teknologi mempengaruhi gaya hidup masyarakat tak terkecuali bidang muamalah. Temuan Cryptocurrency digunakan sebagai alat investasi dan transaksi pembayaran di era modern. Perlunya ijtihad menyikapi kehadiran mata uang digital dalam hukum Islam karena termasuk persoalan baru dan terjadi diskursus ulama kontemporer Indonesia yang menyetujui dan melarangnya. Penelitian bertujuan untuk mengungkap dan menemukan solusi hukum dari penggunaan Cryptocurrency sebagai alat investasi dan pembayaran. Metode penelitian menggunakan studi literature yang bersifat deskriptif-kualitatif. Hasil penelitian menemukan bahwa penggunaan Cryptocurrency sebagai alat investasi tidak boleh digunakan, sebab ada ketidakjelasan objeknya, tidak punya jaminan aset serta tinggi unsur gharar-nya. Sedangkan fungsinya sebagai alat tukar di era digital dalam hukum Islam tidak dilarang dengan syarat yang bertransaksi itu telah sepakat dan saling memahami mekanismenya serta ada legalitas dari pemerintahan.